Ozone Variation at Jabalpur and Inter Relationship Study with Various Meteorological Parameters (Global Journal of Science Frontier Research, 2016)
This paper presents the observations of continuous measurements of surface Ozone (O 3 ) and various meteorological parameters over Jabalpur, M.P, India, from January 2014 to December 2014. The diurnal cycle of surface O 3 concentration exhibited a peak in the afternoon and declined during nighttime on all days of observation. The ozone concentration is influenced by the intensity of solar radiation and chemical reaction between oxides of nitrogen (NOx) and volatile organic compounds (VOC) in the presence of sunlight. This study aims to observe the distribution of the surface zone concentration, characteristics of hourly and daily mean surface ozone with different climatic parameters, such as temperature, relative humidity, and wind speed etc. over Jabalpur. The seasonal variation of ozone showed a unique pattern attaining peak levels in summer and weakening in winter. Higher surface ozone concentrations observed during the summer months of the present study which can be attributed to the high intensity of solar radiation and high temperature levels which promote the photochemical generation of O 3 . The destruction of O 3 is increased during the winter season as a result of scavenging of higher nitrogen oxides.
Keywords: meteorological parameters; surface ozone; ambient NOx; air quality